Association between liver fibrosis scores and cardiovascular disease in elderly based on NHANES 1999–2018 - Man Du; Yuan Li; Jiangtao Du; Jianqiang Song; Shitao Sun; Wanwan Guo; Lifeng Zhu; Shimian Guo (Scientific Reports)
Abstract This study aimed to assess the association between liver fibrosis scores (LFSs) and cardiovascular disease (CVD) in older adults, investigating the mediating effect of total bilirubin (TBil) between LFSs and CVD. Using data from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2018, this cross-sectional study analyzed Americans aged 60 and older. Four LFSs (Forns Score, FIB-4, NAFLD fibrosis score, and BARD Score) were utilized. Weighted logistic regression and smoothed curve fitting explored the relationship between LFSs and CVD. Subgroup analysis assessed this relationship among different populations. Mediation effect analysis examined the role of TBil. This study included 18,902 subjects, with a mean age of 69.64 ± 7.00 years and CVD prevalence of 22.33%. The fully adjusted weighted logistic regression models showed that FS, NFS, FIB-4 and BARD Score were positively associated with CVD with ORs of 1.50 (95% CI:1.37–1.64), 1.50 (95% CI:1.30–1.73), 1.39 (95% CI:1.18–1.64), and 1.54 (95% CI:1.29–1.85). Smoothed curve fitting indicated a nonlinear correlation between LFSs and CVD. Subgroup analysis indicated that the positive associations between FS, NFS, FIB-4, and CVD were consistent with respect to hepatitis B surface antigen, and the positive correlation between FIB-4, BARD Score, and CVD was coherent for the prevalence of hypertension. Mediation analysis revealed TBil mediated 12.61% of the association between FIB-4 and CVD. There exists a positive association between LFSs and CVD in older adults, and TBil mediates the relationship between FIB-4, and CVD. LFSs may serve as a tool for identifying older adults at high risk for cardiovascular disease.